The Effectiveness of Teacher Support for Students’ Learning of Artificial Intelligence Popular Science Activities - Wu, Sheng-Yi; Yang, Kuay-Keng (Frontiers in Psychology, 2022)
The burgeoning of new technologies is increasingly affecting people's lives. One new technology that is heatedly discussed is artificial intelligence (AI) in education. To allow students to understand the impact of emerging technologies on people's future lives from a young age, some popular science activities are being progressively introduced into elementary school curricula. Popular science activities are informal education programs and practices of universal education. However, two issues need to be discussed in the implementation of these activities. First, because these informal curricula are usually short in duration, the question of whether they only serve to generate motivation or actually enhance learning outcomes requires examination. Second, the role of teacher support in popular science activities and its impact on students' learning results need to be further investigated. To this end, this study aims to explore the effectiveness of popular AI science activities in informal curricula on students’ AI achievement and the interrelationship between students' learning outcomes in popular AI science activities with and without teacher support. A six-hour-long AI popular science activity was conducted with 22 5th- and 6th-grade students in elementary school. This study was conducted using a one-group pretest and posttest design, and the data collection tools included AI achievement pre- and posttests and an artifact scoring rubric. The results showed that with regard to learning outcomes, popular science activities were helpful for cognitive enhancement of AI concepts, but more time was needed for skills to improve. Additionally, this study found that students' learning performance was different with and without teacher support. Activities with teacher support can enhance students' learning outcomes, but students become accustomed to relying on their teachers. In contrast, activities without teacher support seem to be more effective in fostering students' independent computational thinking and problem-solving abilities.